COMPARISON OF MANUAL AND AUTOMATIC METHODS IN DETERMINATION OF HEMATOCRIT AND HEMOGLOBIN LEVELS IN GREEN SEA TURTLE - Rindar Mentari Nusanti Putri; Ida Bagus Adnyana; Anak Agung Sagung Kendran (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Sea turtles as protected animals in Indonesia need to recover and increase their population through comprehensive rehabilitation efforts. Examination of hematocrit and hemoglobin in green sea turtles (Chelonia mydas) at the rehabilitation center can function to determine the condition of green sea turtles because arriving turtles have different conditions. Dehydration and anemia in green sea turtles can occur due to transportation of turtles and unsuitable environmental conditions before the turtles were rescued. Examination of hematocrit and hemoglobin can be done manually or using a hematology analyzer. However, automated hematological analysis used for mammals generally not applicable for reptiles including green sea turtles due to the presence of nucleated erythrocytes. This study aims to compare the results of hematocrit and hemoglobin examination in green turtles using manual and automatic methods. This study used blood samples from 10 green turtles at the Turtle Conservation and Education Center (TCEC), Serangan Bali. Then a manual check was carried out at TCEC, Serangan, Bali and automatically using the Vet AutoRead IDEXX tool. Manual hematocrit examination uses the microhematocrit method and manual hemoglobin examination uses the Sahli method. The results were then analyzed using the Statistical Product and Service Solution (SPSS) application. Analysis of the significance of manual and automatic calculations of hematocrit and hemoglobin using paired sample t-test. The results of hematocrit (p=0.972) and hemoglobin (p=0.841) showed no significant difference (p>0.05). It can be concluded that the examination of hematocrit and hemoglobin in green turtles is not different so that it can be done manually and automatically.